Perspectives On Perceived Stigma And Self-Stigma In Patients With Hidradenitis Suppurativa - Koumaki D; Efthymiou O; Bozi E; Katoulis AC (Dove Medical Press, 2019)
Dimitra Koumaki, Ourania Efthymiou, Evangelia Bozi, Alexander C Katoulis Hidradenitis Suppurativa Clinic, 2nd Department of Dermatology and Venereology, “Attikon” General University Hospital, National and Kapodistrian University of Athens, Medical School, Athens, GreeceCorrespondence: Alexander C KatoulisHidradenitis Suppurativa Clinic, 2nd Department of Dermatology and Venereology, “Attikon” General University Hospital, National and Kapodistrian University of Athens, Medical School, Athens, GreeceTel +30-210-5832495Email alexanderkatoulis@yahoo.co.ukObjective: To review current knowledge on how patients with hidradenitis suppurativa (HS) experience stigmatization, as well as on its associations with clinical and psychosocial characteristics of the disease. A better understanding of these may help dermatologists improve screening and management for the benefit of HS patients.Methods: A MEDLINE search using the terms stigmatization, perceived stigma, self-stigma, and HS/acne inversa.Results: Stigmatization is common among HS patients and has a strong psychosocial impact, which is often disproportional to the extent and severity of skin involvement. Stigmatization in HS has many faces and it is more prevalent and more severe than most other skin diseases. Stigmatization of HS patients is due not only to the distressing symptoms of pain, itch malodorous discharge, and disfiguring scars but also to the lack of knowledge about HS on part of the general public.Conclusion: Stigma is a significant contributor to the impairment of quality of life and psychiatric co-morbidities commonly seen in patients with HS. Therefore, evaluation for stigma and formulation of strategies to prevent stigmatization and treat its consequences, in the context of a multidisciplinary approach, may ameliorate considerably the lives of HS patients.Keywords: stigmatization, quality of life, psychosocial, comorbidities